The firm as a Darwin machine: How Generalized Darwinism can further the development of an evolutionary theory of economic growth - J. W. Stoelhorst (Max Planck Institute of Economics, 2010)
The debate on the ontological foundations of evolutionary economics has reached a stage where discussions of these foundations are increasingly leading to the conclusion that there is a need to move from considerations of the general principles of evolutionary theory to the development of concrete middle-range theories of specific economic phenomena. The purpose of this paper is to engage in such an exercise. I explore to what extent the general principles of generalized Darwinism can further the development of an evolutionary theory of economic growth. I will demonstrate the value of generalized Darwinism in two steps. First, by showing how its explanatory logic helps identify some limitations in the seminal theories of economic growth developed by Schumpeter, Penrose, and Nelson and Winter. Second, by showing how the Darwinian logic helps integrate the strengths of these three theories. The result of this exercise is a theory of the firm as a Darwin machine that better captures the interplay of agency and structure in the accumulation of productive knowledge, which is central to the phenomenon of economic growth that Schumpeter, Penrose, and Nelson and Winter set out to explain.
urn:nbn:de:gbv:27-20110628-151953-1
Keywords: 330; Evolutionsökonomik; Wachstumstheorie; Theorie der Unternehmung; Bioökonomik; Theorie